The Role of Physiotherapists on Family Health Teams: Understanding Active Interprofessional Team Members’ Perspectives - Alyssa Benitez; Aly Knox; Brooke Hogben; Adam Ziabari; Phillip Park; Rahul Manikonda; Euson Yeung; Charlotte Anderson (Physiotherapy Canada, 2026)
Abstract Purpose: Family Health Teams (FHTs) were established in 2005 to increase access to health care and collaborative decision-making. It remains unclear how effective this care model is for socio-economically and culturally diverse areas like Scarborough, Ontario. This study aimed to (1) understand administrators’ and practitioners’ perspectives on how FHTs are operating in this region; and (2) illuminate the current and potential roles of physiotherapists within FHTs to address diverse health needs in the Scarborough community. Method: Participants were recruited by snowball and purposive sampling and completed semi-structured interviews. The DEPICT model was used for qualitative data analysis. Results: Ten active members of Scarborough FHTs took part in this study. All participants noted that physiotherapists would be beneficial to FHTs. Three overarching themes emerged from the data: (1) FHT model of care, (2) resource availability and allocation, and (3) competing perspectives on interprofessional collaboration in FHTs. Conclusion: FHTs in underserved areas may benefit from greater integration of physiotherapists to maximize the potential of this care model. Ongoing communication with governing bodies and front-line workers about changing health needs in the community to improve resource allocation and funding is crucial. Increasing diversity within FHTs could better represent the cultural diversity of Scarborough.